(untitled) (Global Journal of Management and Business Research, 2011)
The tourism industry is set to become a major contribution to Terengganu#x2019;s gross domestic product and this will place the second sector to petroleum and gas. Based on that, this paper discusses the relationship of entrepreneurial acculturation, traits, and hospitality management in Terengganu homestay industry. The finding of this study is based on random sampling which covered 86 entrepreneurs who are operating their business in five villages in Terengganu, recommends that for entrepreneurial traits to be effective by certain factors of entrepreneurial acculturation, such as; funding schemes, entrepreneurial programs, physical infrastructure, and advisory service that are considered important should therefore be included. Furthermore, the results indicated that all of respondents are not accepted the factor of entrepreneurial traits become as intermediary variable in a path-model of association entrepreneurial acculturation and hospitality management. Additionally, most of homestay entrepreneurs in Terengganu are not really practicing the factors of entrepreneurial acculturation in developing their entrepreneurial traits and hospitality management.